(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to identify and analyze the impact of official working hours on job satisfaction among women and to determine their levels of satisfaction at the Tripoli International Telecommunications Company, and to present a set of results and recommendations that serve the subject of the study. The researchers relied on what previous studies and research that were concerned with this field addressed. The descriptive-analytical approach was adopted in reaching the study results, and the questionnaire was used as a tool to collect data and information. The study population consisted of 75 individuals, and a purposive random sample of 43 individuals was selected, representing female employees of the Tripoli International Telecommunications Company, covering all job levels. The data, which was analyzed using the SPSS statistical analysis program, revealed a statistically significant relationship between official working hours and job satisfactio among women. One of the most prominent findings was that the company applies the official working hours mechanism to both genders without discrimination. The length of working hours for women is objected to by most working women, and one of the most important recommendations is to reduce the official working hours forwomen in consideration of their physiological condition. The researchers also recommended reducing working hours for women and taking into account the large number of professional and family tasks they have